중소 사업장 근로자의 치석제거 경험 관련요인 - 이재라; Jae Ra Lee; 한미아; Mi Ah Han; 박종; Jong Park; 류소연; So Yeon Ryu; 이철갑; Chul Gab Lee; 문상은; Sang Eun Moon (Chiwisaeng gwahakoeji, 2017)
본 연구는 중소사업장에 종사하는 생산직 근로자를 대상으로 치석제거 경험 관련요인을 알아보기 위해 수행되었다. 조사대상은 광주광역시 188개 중소기업 중 편의추출법으로 5개 사업장을 선정하여 사업장에 근무하는 근로자 455명을 대상으로 자가 보고형 설문조사를 통해 일반적 특성과 근무 관련특성, 치석제거 경험 등을 조사하였다. 빈도분석, t-검정, 교차분석, 다중로지스틱 회귀분석을 이용하여 분석하였다. 대상자의 최근 1년 이내 치석제거 경험은 47.0%였으며, 근로자의 연령이 낮은 경우(aOR, 3.09; 95% CI, 1.60∼5.96), 직위가 높은 경우(aOR, 2.68; 95% CI, 1.55∼4.63), 구강건강에 대한 관심도가 높은 경우(aOR, 2.15; 95% CI, 1.02∼4.52), 최근 1년간 정기적인 구강 검진 경험이 있는 경우(aOR, 2.76; 95% CI, 1.50∼5.11), 치석제거 건강보험 급여화를 인지하고 있는 경우(aOR, 2.91; 95% CI, 1.80∼4.72)가 치석제거 경험의 가능성이 높았다. 결론적으로 치석제거 경험은 47.0%로 비교적 낮았으며, 치석제거 경험에 관련된 요인들은 연령, 직위, 사용 중인 구강관리보조용품, 정기적인 구강검진, 구강질환으로 인한 조퇴 경험, 치석제거 급여화 인지여부였다. 이러한 요인들을 고려하여 근로자의 근무환경 개선 및 치석제거의 인식도 향상을 통해 치석제거 경험률을 높인다면 향후 근로자들의 치주관리에 긍정적인 영향을 미칠 것으로 판단된다. The prevalence of periodontal disease was steadily increased. The best prevention methods for periodontal disease are teeth brushing and scaling. The purpose of this study was to investigate the status of scaling experience and related factors among some workers. Total 455 workers in 5 manufacturing companies in Gwangju were selected using convenience sampling method. General characteristics, work-related characteristics, oral health-related characteristics and scaling experience were collected by self-reported questionnaires. Chi-square tests, t-tests and multiple logistic regression analysis were performed to investigate the factors influencing the scaling experience using SPSS software. Statistical significance was defined as a p-value＜0.05. The proportion of scaling experience during the past year was 47.0%. In simple analysis, age, current working position, number of oral disease, interest in oral health, use of secondary oral products, oral health screening use, oral health education experience and awareness of scaling inclusion in the National Health Insurance (NHI) coverage were associated with scaling experience. Finally, the odds ratios (ORs) for scaling experience were significantly higher in younger subjects (adjusted OR [aOR], 3.09; 95% confidence internal [CI], 1.60∼5.96), assistant manager (aOR, 2.68; 95% CI, 1.55∼4.63), subjects with high interest in oral health (aOR, 2.15; 95% CI, 1.02∼4.52), subjects with oral health screening use (aOR, 2.76; 95% CI, 1.50∼5.11) and awareness of scaling inclusion in the NHI coverage (aOR; 2.91, 95% CI, 1.80∼4.72) in multiple logistic regression analysis. Scaling experience was relatively low (47.0%). The related factors with scaling experience were age, working position, use of screening and awareness of scaling inclusion in the NHI coverage. Considering these factors will increase the utilization rate of scaling.